2016
DOI: 10.1371/journal.pone.0157788
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Immune Effector Functions by Modulating IgG’s Intrinsic Affinity for Target Antigen

Abstract: Antibody-mediated immune effector functions play an essential role in the anti-tumor efficacy of many therapeutic mAbs. While much of the effort to improve effector potency has focused on augmenting the interaction between the antibody-Fc and activating Fc-receptors expressed on immune cells, the role of antibody binding interactions with the target antigen remains poorly understood. We show that antibody intrinsic affinity to the target antigen clearly influences the extent and efficiency of Fc-mediated effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 46 publications
(45 reference statements)
4
44
0
Order By: Relevance
“…To determine how the intrinsic binding affinity of the anti-EGFR arm regulates target selectivity, we constructed an array of affinity-reduced variants of the GA201 mAb by employing alanine mutagenesis to exposed residues in complementarity-determining region (CDR)H3 and L329. The variable domains of three variants exhibiting a ~10–250-fold reduction in affinity compared with the parental sequence were paired with the trastuzumab arm and converted into a DuetMab format.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine how the intrinsic binding affinity of the anti-EGFR arm regulates target selectivity, we constructed an array of affinity-reduced variants of the GA201 mAb by employing alanine mutagenesis to exposed residues in complementarity-determining region (CDR)H3 and L329. The variable domains of three variants exhibiting a ~10–250-fold reduction in affinity compared with the parental sequence were paired with the trastuzumab arm and converted into a DuetMab format.…”
Section: Resultsmentioning
confidence: 99%
“…Alanine mutagenesis of targeted residues in CDRH3 and L3 of the anti-EGFR GA201 mAb was performed by site-directed mutagenesis using standard PCR techniques essentially as described29. For production as human IgG1, V H and V L DNA segments were cloned into an Orip/EBNA-1-based episomal mammalian expression plasmid, pOE as described51.…”
Section: Methodsmentioning
confidence: 99%
“…This has been hypothesized to result from the increased off-rates with lower affinity Fab-antigen interactions, leading to more monovalent Fab-antigen interactions and increased potential for dense IgG opsonization (1 Fc domain per 1 bound Fab domain). In contrast, higher affinity IgGs are more likely to form bivalent interactions with antigen (1 Fc domain per 2 bound Fab domains), limiting the potential for dense IgG binding (117). ADCC mediated by broadly reactive anti-HA mAbs may also be supported through increased affinity between target and effector cell due to broadly neutralizing mAb Fc-FcγRIIIa engagement in conjunction with binding by the viral HA to sialic acids on the effector cell (118).…”
Section: Signaling and Function Of Anti-tumor Antibodiesmentioning
confidence: 99%
“…We recently reported that the intrinsic affinity of antibody to the target antigen directly influenced the extent and efficiency of ADCC. 39 More specifically, using an array of affinity-modulated anti-CD4, epidermal growth factor receptor (EGFR), and human epidermal growth factor receptor 2 (HER2) model mAbs, we have shown that at saturating antibody concentrations, IgG variants with moderate intrinsic affinities (dissociation constant [K D ]~10-150 nM), similar to those generated by the primary humoral immune response, exhibited ADCC that was superior to that of their affinity-improved counterparts (K D ≤1 nM). We further demonstrated that reformatting these high-affinity bivalent IgGs into monovalent formats resulted in substantial augmentation of ADCC.…”
Section: Introductionmentioning
confidence: 99%
“…We further demonstrated that reformatting these high-affinity bivalent IgGs into monovalent formats resulted in substantial augmentation of ADCC. 39 We speculated that IgG antibodies with faster off-rates are likely to dissociate each binding arm more rapidly, resulting in a higher propensity of monovalent engagement with the target cell. This binding mode promotes enhanced opsonization of the target cell, leading to improved recruitment of effector cells.…”
Section: Introductionmentioning
confidence: 99%